New Strait Times, 23 May 2009 - Cruez, Annie Freeda (The New Straits Times Press (M) Bhd, 2009)
Health Minister Datuk Seri Liow Tiong Lai is at his wits' end on how to check the spread of dengue which has claimed 52 lives and infected 20,187 people in the five months of the year.